Plan de negocio para la creación de una microempresa productora de cerveza artesanal en el departamento de Boyacá (2017)
In this project, a feasibility study was carried out for the creation of a microbrewery producing craft beer in the department of Boyacá. This business plan is composed of different chapters that will deal with the following topics: market study, technical study, financial evaluation, organizational structure, environmental impact and social impact. To obtain the viability of the project, a financial evaluation consisting of a statement of results and projected cash flows of 5 years was made, which allowed determining the suitability of the project through the net present value (NPV), the internal rate of return (IRR), and the recovery time of the investment (PR).